Rapid identification and antimicrobial susceptibility testing of positive blood cultures using MALDI-TOF MS and a modification of the standardised disc diffusion test: a pilot study. Issue 11 (27th April 2016) - Fitzgerald, C; Stapleton, P; Phelan, E; Mulhare, P; Carey, B; Hickey, M; Lynch, B; Doyle, M
Abstract : Aims: In an era when clinical microbiology laboratories are under increasing financial pressure, there is a need for inexpensive, yet effective, rapid microbiology tests. The aim of this study was to evaluate a novel modification of standard methodology for the identification and antimicrobial susceptibility testing (AST) of pathogens in positive blood cultures, reducing the turnaround time of laboratory results by 24 h. Methods: 277 positive blood cultures had a Gram stain performed and were subcultured and incubated at 37°C in a CO2 atmosphere for 4–6 h. Identification of the visible growth was performed using matrix-assisted laser desorption time of flight mass spectrometry (MALDI-TOF MS). Taking a modified approach to the Clinical and Laboratory Standards Institute-standardised AST methodology, an inoculum density of 0.5 McFarland was prepared from the early growth for disc diffusion testing. The standard AST method was also performed on the 18–24 h culture. Results: 96% (n=73/76) of gram-negative organisms were correctly identified by MALDI-TOF MS. Comparative analysis of the rapid and standard AST results showed an overall interpretive category error rate of 7.7% (6.7% minor errors, 0.6% major errors and 0.4% very major errors). 100% of Staphylococcus aureus (n=41) and enterococcus isolates (n=9) were correctly identified after 4–6 h incubation. The overall AST categorical agreement was also 100% for these isolates. Conclusions: An incubation of 4–6 h directly from positive blood cultures allowed for both a rapid species identification and an antimicrobial susceptibility result approximately 24 h earlier than is possible using standard methodology.